Enhancing business dynamism and consumer welfare in Costa Rica with regulatory reform - González Pandiella, Alberto (OECD Economics Department Working Papers, 2020)
Regulations of product markets serve legitimate objectives but, when ill-designed, can impose unnecessary restrictions on competition, and therefore on business dynamism, productivity and ultimately well-being. A recent update of the OECD's Product Market Regulation indicator for Costa Rica shows that there is ample room to improve regulations. Costa Rica's economic development is hindered by heavy state involvement and high barriers to entry, compared to both OECD countries and regional peers. This paper discusses options to improve product market regulations, based on international best practices. Regulatory reform can improve consumer welfare by boosting competition and thus lowering prices of key goods and services, which in turn increases the purchasing power of low-income households and reduces poverty. By raising productivity, stronger competition will also allow higher wages. Reducing barriers to entry can facilitate firm creation, boosting investment and jobs